The state of the art as research a strategy to think of ourselves as a university. - Díaz Estévez, Luz Yadira (Rastros Rostros, 2023)
The state of the art as a specific type of research is recent within the research processes. It arose in association with documentary type workers who sought to justify political-administrative decisions within different institutions, and the 1980s could be tentatively considered the time of the genesis of the term "state of the art", at least as far as the social sciences in Latin America are concerned. Initially, the aim was to establish what was known about a topic, with the intention of establishing policies and action alternatives for social development.